Political Authority in Classical Islamic Thought (American Journal of Islam and Society, 1996)
Unlike Christianity, where normative thought is expressed in theologicalwritings, in Islam normative thought is expressed in legal tradition.According to this tradition, the purpose of Islamic society is to submit toGod‘s will, which is expressed clearly through revelation: Human beingsare to create a just society. As political activity is essential for the creationand maintenance of social justice, all political activity is essentially religiousactivity in Islam. Thus, the discussion of political activity is highlydeveloped and wide-ranging in Islamic legal texts. In this paper, I focus ondiscussions of the source of political authority in the ideal Islamic state.Among contempomy commentators on Islam, it has become popularto claim that there is no separation of religion and politics in Islam. Thisclaim, combined with the rejection of secularism by many contemporaryMuslim activists, has led some observers to assume that Islam espouses akind of theocracy. However, this is not the case; the term “nomocracy” ismore suitable to describe Islamic political theory. A theocracy is a stategoverned by God/gods or those who claim to act on divine authority. Anommcy, by contrast, is a state governed by a codified system of laws.The ideal Islamic state is one governed by individuals or bodies bound byIslamic law.’In this context, classical Islamic legal theory implicitly distinguishesbetween those empowered to interpret the law (the legislative and judicialbranches) and those empowered to make sure the law is being followed(the executive branch). Executive political power-with its coerciveauthority-ideally would concern itself with safeguarding Islamic law.But because it is subject to abuse, the formulators of Islam’s classical theoryof political authority considered it an unreliable repository of religious ...